Studio delle prestazioni di giunzioni incollate ibride (Strength evaluation of structural hybrid bonded joints) - F. Moroni (Fracture and Structural Integrity)
The idea of “hybrid joints” arises from the need of joining together materials, producing a tough, stiff and lightweight joint. The core concept is: use two different joining techniques, with the aim to increase the strength and gather the advantages of each technique, reducing the drawbacks. In this work hybrid joints consist in joints produced with two different kinds of joining techniques: one of them being adhesive bonding and the other being one among Resistance Spot Welding, Pop Riveting, Clinching, Self Piercing Riveting. The performance of hybrid joints are compared with those of traditional joints for the single lap joint geometry, for different geometric (plates thickness, pitch of the mechanical fastening) and environmental condition (temperature and ageing). The experimental tests are planned and therefore their results analyzed by means of Design of Experiment techniques. Results show that hybrid joints allow a significant performances enhancement with respect to simple joints when the two simple joining techniques give similar performances, while the performance of hybrid joints are only equal or lower than the those of the strongest joint when the performances of the two joining techniques are significantly different.